PENGARUH SARANA BELAJAR DAN PENGGUNAAN SUMBER BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS X PADA MATA PELAJARAN KEWIRAUSAHAAN DI SMK MUHAMMADIYAH 1 PEKANBARU Ruspadila1,Gimin2, - Ruspadila, Ruspadila; Gimin, Gimin; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this study is to find out how much influence of learning facility and use of learning resource to result of student learning of class X in entrepreneurship subject at SMK Muhammadiyah 1 Pekanbaru. The population of this study is all students of class X SMK Muhammadiyah 1 Pekanbaru with the number 357 with the sample of 189 people, the sample is taken using the technique of Proportional Random Sampling. The data used are primary data and secondary data with data collection methods using questionnaires and documentation. Data analysis technique used is Descriptive Analysis and Multiple Linear Regression Analysis processed through SPSS 17 program. For Windows learning tool facilities in SMK Muhammadiyah 1 Pekanbaru is very adequate that is 51,85% and use of Learning Resources at SMK Muhammadiyah 1 Pekanbaru often used that is 39.15%. Thus it is known that F arithmetic (172,247) > F table (3.045) with Sig. (0,000) <0.05. The meaning is that the means of learning and the use of learning resources together have a significant effect on learning outcomes. Obtained R Square value of 0.649. This means that the percentage of influence of learning facilities and the use of learning resources on learning outcomes is 64.9%. While the remaining 35.1% is influenced by other variables not included in this regression model.Keywords : Learning Facilities, use of Learning Resources, learning outcomes